L'irrationalité dans la prise de décision individuelle: première partie - Fournier, Geneviève; Bujold, Charles (Canadian Journal of Counselling and Psychotherapy, 2012)
This first of two articles approaches the study of the individual decision-makingprocess in a new perspective. The literature concerning various aspects of this process,seen from the psycho-dynamic point of view, is reviewed. Particular emphasis isput upon some perspectives from which decision-making has been studied, certainimportant aspects which are often mentioned in studies of the decisional process,and the individual decision-making, considered sequentially. The questions raisedafter this review concern the irrational aspects that may be involved in decisionmaking,and the factors which are likely to contribute to this irrationality. Thisproblem will be studied in a following article.